Patréla - ALVES, Rodrigo Garcia (2024)
Patréla is a tragic and melancholic story, composed of symboslisms focused on and inspired mainly by Greek tragedies and Aristotle’s concept of tragedy described in his book Poetics. This memorial describes the use of RPG (Roleplaying game) to write a script through the immersion provided by it, where the author calls some of his friends who became co-authors of the work through their characters, choices and contributions to the world. This work explains the game methods used to make it possible, from the creation of the world, the characters, rules and agréments necessary for the narrative to happen. RPG is a game where people come together to tell a story, it’s a collaborative narrative, a piece of postmodern literature that is hardly observed as such due to the myth of paidea being a form of play for children Only. With the studies of Caillois (1990), Huizinga (1951) and Murray (2003) the author describes and analyzes the concepts of Paidea and Agency within the RPG, as well as uses Nephew (2003) and Huntchinson (1983) to sustain the post modern aspects of the game.